The Development Trend of China's Agricultural Product Cold Chain Logistics from the Perspective of Big Data. (17th November 2022) - Wang, Shenxiang
Abstract : With the gradual prosperity of social economy, people's demand for agricultural products consumption has also gradually increased. Through the efficient introduction of big data technology, we can optimize and innovate the management system of agricultural cold chain logistics enterprises, realize the modernization of enterprise logistics management, and effectively improve the management efficiency of agricultural cold chain logistics enterprises. Using big data technology can improve the efficiency of information docking, improve the stickiness of enterprise customers, and speed up the value-added of cold chain logistics data. This study introduces the common clustering algorithms in the field of cold chain logistics, with emphasis on the spectral clustering algorithm. The spectral clustering algorithm not only reduces the error rate but also significantly reduces the time spent in the clustering process, which shows the effectiveness and feasibility of the application of spectral clustering algorithm in China's agricultural cold chain logistics industry.